Factors Affecting the Decision to Use Just-In-Time Method for Precast Components in Surabaya Construction Industry - Vinza Firqinia Fristia; Trijoko Wahyu Adi (Institut Teknologi Sepuluh Nopember, 2017)
Lack of management of precast components lead to decreased productivity of work. The use of Just-In-Time (JIT) method in construction projects aimed to reduce production costs, improved quality, and increased productivity. However, not all construction companies implement JIT on the Surabaya construction project. This study aimed to identify factors that influence to use JIT method decisions for precast components in Surabaya construction company. Data from questionnaires were collected and analysed using Relative-Importance-Index analysis and Confidence-Interval. The results of research that Surabaya construction company have knew and understood but still not implemented. Factors that influence at construction project were planning and efficient communication between all stakeholders.Kurangnya pengelolaan komponen pracetak mengakibatkan produktivitas kerja menurun. Penggunaan metode Just-In-Time (JIT) dalam proyek-proyek konstruksi bertujuan mengurangi biaya produksi, meningkatkan kualitas dan produktivitas. Namun, tidak semua perusahaan konstruksi menerapkan pada proyek konstruksi kota Surabaya. Penelitian ini bertujuan mengidentifikasi faktor-faktor yang mempengaruhi keputusan menggunakan metode JIT untuk komponen pracetak dalam perusahaan konstruksi kota Surabaya. Data dari kuesioner dikumpulkan dan dianalisis menggunakan analisis Relative-Importance-Index dan confidence-interval. Hasil penelitian bahwa perusahaan konstruksi Kota Surabaya telah mengetahui dan memahami namun masih belum menerapkan. Faktor yang mempengaruhi dalam proyek konstruksi ialah perencanaan dan komunikasi secara efisien antara semua pemangku kepentingan.